Penerapan Data Mining Prediksi Nilai UN Siswa SMP Menggunakan Metode Naive Bayes - miftahul jannah (I N F O R M A T I K A, 2020)
Examination National (UN) is conducted every year at all levels of education one SMP N 8 Mandau. The data of Examination National (UN) of students in SMP N 8 Mandau each year increases and is stored in the form of Soft file and Hard file. From the last few years the value of students UN in SMP N 8 is not stable. High and low the value of students UN greatly affect the quality of schools. To overcome this required a data mining technique with naive bayes method in predicting the value of UN students based on student data of 2016 and 2017. Of the 10 test data get predicted 7 people matching the data in 2017. So it has an accuracy of 70%. So this method can be applied in predicting the value of future UN students.